New insights into the climate of northern Iberia during the Younger Dryas and Holocene: The Mendukilo multi-speleothem record. (1st April 2023) - Bernal-Wormull, J.L.; Moreno, A.; Bartolomé, M.; Arriolabengoa, M.; Pérez-Mejías, C.; Iriarte, E.; Osácar, C.; Spötl, C.; Stoll, H.; Cacho, I.; Edwards, R.L.; Cheng, H.
Abstract: Recent hydroclimate studies on the Iberian Peninsula have shown a complex regional pattern in timing and intensity of climate change spanning the Younger Dryas and the Holocene. These changes are due to multifaceted interactions between climate variability that characterizes the Atlantic Ocean region and hydroclimatic processes associated with the Mediterranean climate, thus making it difficult to reconstruct centennial- and millennial-scale variability in rainfall. In this study we present a composite and continuous isotopic record (δ 13 C and δ 18 O) consisting of four stalagmites from Mendukilo cave (MEN composite) in the western Pyrenees covering the Younger Dryas and the entire Holocene. This record reveals millennial-scale shifts in carbon isotopes in response to changes in the hydroclimate in the northern part of Iberia. The MEN oxygen isotopes show little variation on millenial time scales but reveal centennial changes that correlate with North Atlantic events (e.g., the 8.2 kyr BP cooling event). We observe a delay in the onset of humid conditions in the early Holocene and a subsequent trend towards drier and colder conditions between 6.0 and 2.5 kyr BP. This new, high-resolution and replicated speleothem record denotes the complex connection that exists between the North Atlantic and Western Europe during last millennia and the strong regional heterogeneity of the hydroclimate of Iberia during this time. Highlights: Younger Dryas and Holocene climate variability has been addressed by multiple proxies from a replicated stalagmite record. Millenial-scale carbon isotope variability of the record is driven by climatic processes controlling soil pCO2 . Centennial-scale oxygen isotope abrupt changes are associated with meltwater discharges into the North Atlantic.